EFEKTIVITAS PENGGUNAAN TEKNOLOGI DIGITAL TERHADAP MOTIVASI BELAJAR PESERTA DIDIK - Nastiti, Alfia Galih Nini; Sri Sumartiningsih; Agus Yuwono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to examine the effectiveness of using digital technology in increasing students' learning motivation. In today's digital era, technology has become an integral part of the learning process, which has a significant impact on the way students access information and interact with learning material. This research uses a quantitative approach with an experimental design to measure changes in student learning motivation after implementing digital technology in the learning process. The research subjects consisted of students in several junior high schools who were divided into two groups, namely an experimental group that used digital technology and a control group that used conventional learning methods. Data was collected through questionnaires filled out by students before and after implementing digital technology. The research results show that the use of digital technology can significantly increase students' learning motivation, especially in terms of interest and involvement in learning. By using interesting and interactive digital media, students become more active and motivated to learn. This research provides the implication that the appropriate use of digital technology can be an effective tool in increasing student learning motivation in the current era of digital education.